Bonding effects of cleaning protocols and time-point of acid etching on dentin impregnated with endodontic sealer - Manzoli, Tatiane Miranda [UNESP]; Zaniboni, Joissi Ferrari [UNESP]; Besegato, Joao Felipe [UNESP]; Guiotti, Flavia Angelica [UNESP]; Rached Dantas, Andrea Abi [UNESP]; Kuga, Milton Carlos [UNESP] (Korean Acad Conservative Dentistry, 2022)
Objectives: This study aimed to investigate the bonding effects of cleaning protocols on dentin impregnated with endodontic sealer residues using ethanol (E) or xylol (X). The effects of dentin acid etching immediately (I) or 7 days (P) after cleaning were also evaluated. For bonding to dentin, universal adhesive (Scotchbond Universal; 3M ESPE) was used. The persistence of sealer residues, hybrid layer formation and microshear bond strength were the performed analysis. Materials and Methods: One hundred and twenty bovine dentin specimens were allocated into 4 groups (n = 10): G1 (E+I); G2 (X+I); G3 (E+P); and G4 (X+P). The persistence of sealer residues was evaluated by SEM. Confocal laser scanning microscopy images were taken to measure the formed hybrid layer using the Image J program. For microshear bond strength, 4 resin composite cylinders were placed over the dentin after the cleaning protocols. ANOVA followed by Tukey test and Kruskal-Wallis followed by Dunn test were used for parametric and non-parametric data, respectively (alpha = 5%). Results: G2 and G4 groups showed a lower persistence of residues (p < 0.05) and thicker hybrid layer than the other groups (p < 0.05). No bond strength differences among all groups were observed (p > 0.05). Conclusions: Dentin cleaning using xylol, regardless of the time-point of acid etching, provided lower persistence of residues over the surface and thicker hybrid layer. However, the bond strength of the universal adhesive system in etch-and-rinse strategy was not influenced by the cleaning protocols or time-point of acid etching.
Keywords: Adhesives; Confocal; Dentin; Ethanol; Solvents